Imaging anti-angiogenic treatment response with DCE-VCT, DCE-MRI and DWI in an animal model of breast cancer bone metastasis - Bäuerle, Tobias; Bartling, Sönke; Berger, Martin R.; Schmitt-Gräff, Annette; Hilbig, Heidegard; Kauczor, Hans-Ulrich; Delorme, Stefan; Kiessling, Fabian (European journal of radiology, 2010)
As current classification systems for the assessment of treatment response in bone metastasis do not meet the needs of oncologists, new imaging biomarkers are desirable. Therefore, the diagnostic impact of dynamic contrast enhanced (DCE)-volumetric computed tomography (VCT) (descriptive analysis), DCE-MRI (two-compartment model) and diffusion weighted imaging (DWI) for monitoring anti-angiogenic therapy effects of the VEGF antibody bevacizumab in breast cancer bone metastases in rats was studied. Nude rats (n=8 animals treated with bevacizumab and n=9 untreated control rats) with site-specific osteolytic bone metastasis of the hind leg were imaged with a 1.5T clinical MRI-scanner in an animal coil as well as in a volumetric CT-scanner at days 30, 40, 50 and 60 after inoculation of MDA-MB-231 human breast cancer cells. From these data, osteolytic lesion size (OLS), peak enhancement (PE), area under the curve (AUC), amplitude (A), exchange rate constant (kep) and apparent diffusion coefficient (ADC) were determined in bone metastases. Prior to changes in OLS (p≤0.05 at days 50 and 60) there was already a significant decrease in PE, AUC and A (p≤0.05 at days 40-60) in treated animals compared to controls. However, for kep and ADC there were no significant differences between the groups at any time point (p>0.05 at days 40-60). In conclusion, anti-angiogenic treatment response in osteolytic breast cancer bone metastases can be assessed early with surrogate markers of vascularization, while DWI appears to be insensitive.